Position of Acting Land Acting Officer in Collecting Customs for Land and Building Rights (Study in Mataram City) (International Journal of Scientific Research and Management (IJSRM), 2019)
In carrying out its duties related to the making of deeds, the Land Deed Maker Officer (PPAT) is directly in contact with tax issues because the procedure for making a deed requires payment of taxes before the deed can be signed. According to the provisions in the collection of Customs and Land Rights (BPHTB) collection fees using a self-assessment system, but in the implementation of calculations and deposits to the regional treasury it is not often entrusted by the taxpayer to PPAT. The problems discussed in this study are about the implementation of BPHTB collection in the city of Mataram and how the position of PPAT in implementing BPHTB collection. This research is empirical legal research with the consideration of obtaining a direct description of the role of PPAT in implementing BPHTB collection in the city of Mataram. The approach used is the legislative approach, conceptual approach, sociological approach. Data collection techniques by conducting studies in the field in the form of interviews, then processing data and analyzed descriptively qualitatively so that answers to existing problems are obtained. Based on the results of the study it can be concluded that the implementation of BPHTB collection in Mataram City is still done conventionally, namely the taxpayer completes the Regional Tax Deposit Form - the Land Acquisition Fee (SSPD-BPHTB) and submits it manually to the Regional Finance Agency (BKD) of Mataram City to do the verification process, then the taxpayer makes a payment through the reception counter at the BKD Office in the City of Mataram. The position of PPAT in BPHTB collection is as an authorized official in fulfilling BPHTB services, the intention is that PPAT in carrying out its position as a public official authorized to make a transfer deed of land rights has the right to refuse a deed if it is not submitted proof of BPHTB payment.